Release characteristics of enoxaparin sodium-loaded polymethylmethacrylate bone cement - Hui Sun; Xinzhe Ma; Zhiyong Li; Jianning Liu; Wei Wang; Xiangbei Qi (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background This study aimed to prepare the polymethylmethacrylate (PMMA) bone cement release system with different concentrations of enoxaparin sodium (ES) and to investigate the release characteristics of ES after loading into the PMMA bone cement. Methods In the experimental group, 40 g Palacos®R PMMA bone cement was loaded with various amount of ES 4000, 8000, 12,000, 16,000, 20,000, and 24,000 AXaIU, respectively. The control group was not loaded with ES. Scanning electron microscopy (SEM) was used to observe the surface microstructure of the bone cement in the two groups. In the experiment group, the mold was extracted continuously with pH7.4 Tris-HCL buffer for 10 days. The extract solution was collected every day and the anti-FXa potency was measured. The experiment design and statistical analysis were conducted using a quantitative response parallel line method. Results Under the SEM, it was observed that ES was filled in the pores of PMMA bone cement polymer structure and released from the pores after extraction. There was a burst effect of the release. The release amount of ES on the first day was 0.415, 0.858, 1.110, 1.564, 1.952, and 2.513, respectively, from the six groups with various ES loading amount of 4000, 8000, 12,000, 16,000, 20,000, and 24,000 AXaIU, all reaching the peak of release on the first day. The release decreased rapidly on the next day and entered the plateau phase on the fourth day. Conclusion The prepared ES-PMMA bone cement has high application potential in orthopedic surgery. ES-PMMA bone cement shows good drug release characteristics. The released enoxaparin sodium has a local anti-coagulant effect within 24 h after application, but it will not be released for a long time, which is complementary to postoperative anti-coagulation therapy.